Shale alteration after exposure to supercritical CO2 - Rezaee, M. Reza; Saeedi, Ali; Iglauer, S.; Evans, B. (Elsevier, 2017)
Caprock seal efficiency evaluation is a vital part of the assessment of any CO2 storage site. The main goal of this study was to examine the dynamic seal capacity of several intra-formational shale units in the Latrobe Group in the Gippsland Basin, Australia and to characterise their caprock sealing efficiency before and after exposure to supercritical CO2 (scCO2). This laboratory study examined changes to the mineralogical composition of the shale, capillary threshold pressure, and pore size distribution before and after being exposed to scCO2 at reservoir conditions utilizing several analytical methods. Samples selected for this study were taken from cores that have been stored in a sample facility. Since the original mineralogy of the samples is likely to have changed over time at surface storage conditions, thus chemical reactions may be different if fresh samples could have been analysed. X-ray diffraction (XRD) and scanning electron microscopy (SEM) indicate that there are several chemical reactions that occurred between rock-forming minerals and the brine-scCO2 system. Chemical reactions include dissolution and precipitation of several authigenic minerals such as kaolinite, natrojarosite, silica and gypsum. Mercury injection capillary pressure (MICP) and nuclear magnetic resonance (NMR) measurements indicate a reduction in the capillary threshold pressures and an increase in pore volume for most of the samples exposed to scCO2.